An Elastic Optical Network-based Architecture for the 5G Fronthaul - Riva, Mateus; Donâncio, Henrique; Almeida, Felipe R.; Figueiredo, Gustavo B.; Tinini, Rodrigo I.; Cesar Jr., Roberto M.; Batista, Daniel M. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2018)
In 5G networks, the traffic demands are expected to increase significantly. To deal with this problem, many research efforts focus on TWDMPON for the fronthaul. However, TWDM-PON suffers from the issue of wasted bandwidth when a demand is smaller than the channel. In order to avoid this inefficiency, we propose an OFDM-PON supported architecture for the Cloud Radio Access Network (C-RAN) topology to implement the technology of elastic optical networks into C-RAN. Experiments show that OFDM-PON allows for improved usage of the bandwidth (between 145% and 218% improvement), similar average wait time for requests (average difference below 7%), and similar request loss (average difference below 2%) in comparison to TWDM.